Expanded morphological description of the Pawang Bent-toed Gecko Cyrtodactylus disjunctus of Thailand and a new country record for Malaysia - Akil, Mohd Abdul Muin Md; Hong, Zijia; Sah, Shahrul Anuar Mohd; Ramli, Raiandy; Grismer, L. Lee (Zootaxa, 2025)
Reported here is the first record of Cyrtodactylus disjunctus from Peninsular Malaysia. The specimen was collected in a limestone forest at Tasik Meranti, Perlis, approximately 13 km southeast of its type locality in Thailand. The specimen is an adult male which provides us the opportunity to not only add to the variation of this species but document sexually dimorphic characters. This report underscores how much remains undiscovered, even in areas as well-surveyed as Perlis State Park.